## Simplifying the Expression: (7m^-2m^2n)^2

This expression involves exponents, multiplication, and negative exponents. Let's break down the simplification process step-by-step.

### 1. Combining like terms within the parentheses:

**m^-2 * m^2 = m^( -2 + 2) = m^0 = 1**(Remember: Any number raised to the power of 0 equals 1)**Therefore, (7m^-2m^2n) becomes (7 * 1 * n) = 7n**

### 2. Applying the exponent to the simplified term:

**(7n)^2 = 7^2 * n^2 = 49n^2**

### Final answer:

The simplified expression of (7m^-2m^2n)^2 is **49n^2**.